Rule Following, Standards of Practice, and Open-mindedness - Johnston, James Scott (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
In this paper, I discuss the Ontario College of Teachers’ most recent versions of the Standards of Practice with William Hare’s counsel on being open-minded regarding open-mindedness in mind. Specifically, I insist that the use of the Standards of Practice as guidelines for working through cases of professional and ethical issues requires yet another rule to indicate when to deviate from this or that standard. In this way, open-mindedness consists of developing and following rules to indicate when and where specific standards should be bypassed. These rules vary, however, one source of these can be found in what Barbara Herman has called, “Rules of Moral Salience”—rules that guide us in our day-to-day moral decision-making and that we draw on when called upon to make moral-ethical judgments. What this means for various ethics (ethics of care; Kantian-type ethics, psychological and/or developmental accounts of ethics) is also broached.